Exploration of altered miRNA expression and function in MSC-derived extracellular vesicles in response to hydatid antigen stimulation - Wang, Xin; Mijiti, Wubulikasimu; Jia, Qiyu; Yi, Zhifei; Ma, Junchao; Zhou, Ziyu; Xie, Zengru (Frontiers in Microbiology, 2024)
Background Hydatid disease is caused by Echinococcus parasites and can affect various tissues and organs in the body. The disease is characterized by the presence of hydatid cysts, which contain specific antigens that interact with the host’s immune system. Mesenchymal stem cells (MSCs) are pluripotent stem cells that can regulate immunity through the secretion of extracellular vesicles (EVs) containing microRNAs (miRNAs). Methods In this study, hydatid antigens were isolated from sheep livers and mice peritoneal cavities. MSCs derived from mouse bone marrow were treated with different hydatid antigens, and EVs were isolated and characterized from the conditioned medium of MSCs. Small RNA library construction, miRNA target prediction, and differential expression analysis were conducted to identify differentially expressed miRNAs. Functional enrichment and network construction were performed to explore the biological functions of the target genes. Real-time PCR and Western blotting were used for miRNA and gene expression verification, while ELISA assays quantified TNF, IL-1, IL-6, IL-4, and IL-10 levels in cell supernatants. Results The study successfully isolated hydatid antigens and characterized MSC-derived EVs, demonstrating the impact of antigen concentration on MSC viability. Key differentially expressed miRNAs, such as miR-146a and miR-9-5p, were identified, with functional analyses revealing significant pathways like Endocytosis and MAPK signaling associated with these miRNAs’ target genes. The miRNA-HUB gene regulatory network identified crucial miRNAs and HUB genes, such as Traf1 and Tnf, indicating roles in immune modulation and osteogenic differentiation. Protein–protein interaction (PPI) network analysis highlighted central HUB genes like Akt1 and Bcl2. ALP activity assays confirmed the influence of antigens on osteogenic differentiation, with reduced ALP activity observed. Expression analysis validated altered miRNA and chemokine expression post-antigen stimulation, with ELISA analysis showing a significant reduction in CXCL1 expression in response to antigen exposure. Conclusion This study provides insights into the role of MSC-derived EVs in regulating parasite immunity. The findings suggest that hydatid antigens can modulate the expression of miRNAs in MSC-derived EVs, leading to changes in chemokine expression and osteogenic capacity. These findings contribute to a better understanding of the immunomodulatory mechanisms involved in hydatid disease and provide potential therapeutic targets for the development of new treatment strategies.